1979
DOI: 10.1289/ehp.28-1637502
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and accumulation of cadmium in populations from Japan, the United States, and Sweden

Abstract: Studies were carried out in Japan, United States, and Sweden regarding comparability of analytical methods for cadmium, daily intake of cadmium via food, daily amount of cadmium in feces, concentrations of cadmium in different tissues and the body burden of cadmium, urinary excretion of cadmium and cadmium concentrations in blood. It was found that the cadmium intake via food among adults is about 35 mug/day in Japan (Tokyo) and about 17 mug/day in the U.S. (Dallas) and Sweden (Stockholm). It varies with age i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(39 citation statements)
references
References 28 publications
9
30
0
Order By: Relevance
“…Also the distribution pattern obtained in the current study demonstrated that Cd is more retained in liver than Pb, when both the metals given individually. This observation supports the fact that the Cd halflife in human body is more than 30 years [32]. The decreased activity of catabolizing enzyme could also be attributed to decreased availability of steroids.…”
Section: Discussionsupporting
confidence: 83%
“…Also the distribution pattern obtained in the current study demonstrated that Cd is more retained in liver than Pb, when both the metals given individually. This observation supports the fact that the Cd halflife in human body is more than 30 years [32]. The decreased activity of catabolizing enzyme could also be attributed to decreased availability of steroids.…”
Section: Discussionsupporting
confidence: 83%
“…However, in the already mentioned international study (Vahter, 1982), the exposed and past-exposed to nonexposed to smoking ratio was 1.1 for Japan compared to 4.1 in our study. The smokers to nonsmokers ratio was 4.94 in the present study as compared to 2.0 in the United States (Kowal et al, 1979;Kjellström, 1979). Thus, the hypothesis that a factor other than the sole cadmium content in cigarette is responsible for the discrepancy, as was observed, is a more important mechanism for blood cadmium contamination (Benedetti et al, 1994;Rey et al, 1997).…”
Section: Cadmium In the Organs And Tissues Of Canadians 159supporting
confidence: 40%
“…However, the most striking data obtained from a Canadian population were those of Le Baron et al (1977), with levels greater than any other reported in the world at this time, with the exception of data from Japan (Kjellström, 1979). Some explanations for these elevated concentrations of cadmium in kidney may include the extreme care exercised in the selection of cortex and medulla samples, and the distribution of age groups; although age extremes were 10 to 85 yr, most of the subjects were in the group age 30-69 yr (82%), with 60% of this last section falling in the age group 50-59 yr where maximal cadmium concentration is expected.…”
Section: Please Scroll Down For Articlementioning
confidence: 60%
“…Cadmium can enter the body through tobacco smoking, diet, drinking water, and inhaling it from the air. Small amounts of Cd taken over many years may cause kidney damage and fragile bones, since Cd is mainly stored in bone, liver and kidneys (Kjellström, 1979;Nriagu, 1981). Furthermore, Cd causes stomach irritation, vomitting, and diarrhoea.…”
Section: Introductionmentioning
confidence: 99%